Deconstruction of Binary Opposition in Kritikus Adinan Story by Budi Darma - Iswadi Bahardur (Universitas Tidar, 2018)
Writing this article backed by multi interpretation problems raised by a text, especially literary texts. Multi interpretation is inseparable from the consciousness and unconscious of the subject of the author, as well as the process of reconstruction by the reader. Based on this article this article aims to describe the results of deconstructing binary opposition readings on the story of Kritikus Adinan by Budi Darma. The data source used is the story of Kritikus Adinan. The research method used is descriptive analysis with the theoretical perspective of deconstruction of Jaques Derrida. Based on the findings and data analysis, the results show the following. First, the deconstruction readings of the Kritikus Adinan can not be separated from the word-scoring process as Jaques Derrida puts it in deconstruction theory. Secondly, the reconstruction of Kritkus Adinan’s story leads to unfamiliarity but leads the reader to discover the marginalized texts. Third, based on the results of deconstruction reading in the story of Kritikus Adinan, there is a binary opposition that has been denied and broken by the author by presenting a reversal of fact. Suggestions that can be recommended are many other literary works that are worthy and important to be reviewed by other researchers to uncover the phenomenon of reversing the facts by the author.